Estimating and Testing Dynamic Corporate Finance Models - Bazdresch, Santiago; Kahn, R. Jay; Whited, Toni M. (Review of Financial Studies, 2018)
We assess the finite sample performance of simulation estimators that are used to estimate the parameters of dynamic corporate finance models. We formulate an external validity specification test and propose a new set of statistical benchmarks that can be used to estimate and evaluate these models. These benchmarks are based on model policy functions. Our Monte Carlo simulations show that the estimators are largely unbiased with low root mean squared errors. When computed with an optimal weight matrix, the specification tests associated with the estimators are close to correctly sized. These tests have excellent power to detect misspecification. Received August 19, 2016; editorial decision May 30, 2017 by Editor Stijn Van Nieuwerburgh.